Peningkatan Literasi AI dan Pemanfaatan Prompting Artificial Intelligence Untuk Keterampilan dan Kreativitas Siswa SMK Negeri 3 Sigli - Tri Mulya Dharma (Universitas Dirgantara Marsekal Suryadarma, 2026)
The rapid advancement of Artificial Intelligence (AI) requires students to possess digital literacy. However, initial identification of 10 11th-grade DKV students at SMK Negeri 3 Sigli revealed prompting-writing limitations and a lack of structured AI training due to manual design methods. This Community Service (PKM) program, conducted on July 13, 2026, aimed to enhance AI literacy and prompting techniques for product content creation. The learning by doing method combined theoretical lectures with practical mentoring using Gemini AI. Progress was evaluated via Quizizz pre-tests and post-tests, measuring AI literacy concepts and technical prompting formulation. Quantitative results showed students average AI literacy understanding increased from 30% to 80%, while prompting skills rose from 10% to 65%. This training successfully equipped students with creative, safe, and responsible AI prompting capabilities.